Infertility, Gendered Expectations, and Marital Breakdown: A Socio-Legal Analysis of Childlessness as a Ground for Divorce in Indonesia - Justine Ardalia Maharani (Baileo: Jurnal Sosial Humaniora, 2026)
This study aims to analyze how reproduction-oriented social expectations influence legal reasoning and social legitimacy in divorce cases arising from childlessness in Indonesia. In a society deeply rooted in patriarchal and religious values, infertility is often perceived not merely as a biological issue but as a moral and social failure. Employing a qualitative approach through a socio-legal research design, this study combines normative analysis of Islamic family law with a sociological examination of gender and reproductive constructions. Data were collected from the Situbondo Religious Court Decision No. 1254/Pdt.G/2021/PA. Situbondo and in-depth interviews with judges, lawyers, and parties involved in divorce cases due to infertility. The findings reveal that infertility is socially interpreted as the wife’s inability to fulfill reproductive duties, generating psychological pressure, social stigma, and legitimized divorce through judicial reasoning framed as “disharmony” or “no hope of reconciliation,” despite the absence of explicit legal grounds in Law No. 1/1974 or the Compilation of Islamic Law. A new tendency among younger judges reflects an emerging view of infertility as a gender equality and individual rights issue. The novelty of this study lies in integrating legal and sociological analysis to uncover the silent patriarchal bias within contemporary Islamic legal practice. Theoretically, it advances socio-legal and family sociology discourse by demonstrating that law is not neutral but a site of social and gender negotiation, while practically, it advocates mainstreaming gender equality perspectives in marital law interpretation to achieve substantive justice in infertility-related divorces.